LOCAL POLITICAL COMMUNICATION STRATEGY IN IMPROVING VILLAGE PUBLIC SERVICE PERFORMANCE - Prayitno, Arief (JWP (Jurnal Wacana Politik), 2024)
The public considers that bureaucratic performance in public services is still low, by listening to community voices, village governments can be more responsive and adaptive to local conditions and needs. This research aims to analyze local political communication strategies implemented by village governments in improving the performance of village public services. This research used qualitative methods with a descriptive approach which allows researchers to understand and explain phenomena in depth in a natural context, data was obtained from primary data, through interview, and secondary data, through official documents, journal and media. The research results show that effective political communication is very important to improve the performance of public services at the village government level. Strategies such as increasing transparency through various communication channels, involving the community through village meetings and discussion forums, and using digital technology can speed up interactions and ensure citizen involvement. Increasing the competency of village officials in communication skills and public service ethics is also crucial for creating responsive and accountable services. Promotion of village program results and achievements can strengthen community trust and encourage active participation in development. However, various challenges such as limited resources, policy incompatibility between the village and national levels, slow bureaucratic processes, and local political dynamics such as group competition and political intervention, still hamper the effectiveness of public services. Low community participation in decision making and monitoring also reduces the sense of ownership and responsibility for village programs, resulting in dissatisfaction and reduced program effectiveness.